EU Solidarity and Policy in Fighting Infectious Diseases: State of Play, Obstacles, Citizen Preferences and Ways Forward. - Anniek de Ruijter; Roel Beetsma; Brian Burgoon; Francesco Nicoli; Frank Vandenbroucke (Center for Economic Studies and ifo Institute (CESifo), 2020)
In this paper we confront the role the EU traditionally plays in the domain of health with the urgent need for collective action triggered by the corona virus pandemic. In the face of such a crisis, we argue that the joint procurement, stockpiling and allocation of medical countermeasures is a key component of true European solidarity, besides maintaining the integrity of the Single Market. We present the first results of a survey experiment taken before the current crisis on citizens' attitudes towards centralizing at the EU level of policies to combat infectious diseases, which indicates considerable support. We conclude that a more robust policy framework with substantial centralization of procurement, stockpiling and allocation is warranted.
Keywords: I10; I18; 330; Covid-19; medicines; European Union; centralization